Effects of running on the development of knee osteoarthritis: An updated systematic review at short-term follow-up - Dhillon, J.; Krautler, M. J.; Belk, J. W.; Scillia, A. J.; McCarthy, E. C.; Ansah-Twum, J. K.; McCulloch, P. C. (Orthopaedic Journal of Sports Medicine, 2023)
Background: Some studies have suggested that running increases the risk of knee osteoarthritis (OA), while others believe it serves a protective function. Purpose: To perform an updated systematic review of the literature to determine the effects of running on the development of knee OA. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review was performed by searching the PubMed, Cochrane Library, and Embase databases to identify studies evaluating the effect of cumulative running on the development of knee OA or chondral damage based on imaging and/or patient-reported outcomes (PROs). The search terms used were "knee AND osteoarthritis AND (run OR running OR runner)." Patients were evaluated based on plain radiographs, magnetic resonance imaging (MRI), and PROs (presence of knee pain, Health Assessment Questionnaire-Disability Index, and the Knee injury and Osteoarthritis Outcome Score). Results: Seventeen studies (6 level 2 studies, 9 level 3 studies, and 2 level 4 studies), with 7194 runners and 6947 nonrunners, met the inclusion criteria. The mean follow-up time was 55.8 months in the runner group and 99.7 months in the nonrunner group. The mean age was 56.2 years in the runner group and 61.6 years in the nonrunner group. The overall percentage of men was 58.5%. There was a significantly higher prevalence of knee pain in the nonrunner group (P < .0001). Although 1 study found a significantly higher prevalence of osteophytes in the tibiofemoral (TF) and patellofemoral (PF) joints within the runner group, multiple studies found no significant differences in the prevalence of radiographic knee OA (based on TF/PF joint-space narrowing or Kellgren-Lawrence grade) or cartilage thickness on MRI between runners and nonrunners (P > .05). One study found a significantly higher risk of knee OA progressing to total knee replacement among nonrunners (4.6% vs 2.6%; P = .014). Conclusion: In the short term, running is not associated with worsening PROs or radiological signs of knee OA and may be protective against generalized knee pain.